Variation in quality of preventive care for well adults in Indigenous community health centres in Australia - Bailie, R.; Si, D.; Connors, C.; Kwedza, R.; O'Donoghue, L.; Kennedy, C.; Cox, R.; Liddle, H.; Hains, J.; Dowden, M.; Burke, H.; Brown, A.; et al. (BioMed Central, 2011)
Background: Early onset and high prevalence of chronic disease among Indigenous Australians call for action on prevention. However, there is deficiency of information on the extent to which preventive services are delivered in Indigenous communities. This study examined the variation in quality of preventive care for well adults attending Indigenous community health centres in Australia. Methods: During 2005-2009, clinical audits were conducted on a random sample (stratified by age and sex) of records of adults with no known chronic disease in 62 Indigenous community health centres in four Australian States/Territories (sample size 1839). Main outcome measures: i) adherence to delivery of guideline-scheduled services within the previous 24 months, including basic measurements, laboratory investigations, oral health checks, and brief intervention on lifestyle modification; and ii) follow-up of abnormal findings.Results: Overall delivery of guideline-scheduled preventive services varied widely between health centres (range 5-74%). Documentation of abnormal blood pressure reading ([greater than or equal to]140/90 mmHg), proteinuria and abnormal blood glucose ([greater than or equal to]5.5 mmol/L) was found to range between 0 and > 90% at the health centre level. A similarly wide range was found between health centres for documented follow up check/test or management plan for people documented to have an abnormal clinical finding. Health centre level characteristics explained 13-47% of variation in documented preventive care, and the remaining variation was explained by client level characteristics. Conclusions: There is substantial room to improve preventive care for well adults in Indigenous primary care settings. Understanding of health centre and client level factors affecting variation in the care should assist clinicians, managers and policy makers to develop strategies to improve quality of preventive care in Indigenous communities.